Actualization of Fisip Unila’s Partnership with Atpusi Lampung Province Through Personal Rebranding Training for Librarians in the Era of Artificial Intelligence - Ida Nurhaida; Andi Windah; Nina Yudha Aryanti; Arif Sugiono (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: In the contemporary landscape characterized by advancements in artificial intelligence (AI), the profession of librarianship is experiencing a noteworthy transformation, thereby necessitating a re-evaluation and re-branding of the role in order to maintain its relevance. Librarians are transitioning from their traditional role as custodians of physical books to emerging as essential stakeholders in the domains of digital literacy, privacy, and information ethics. They currently fulfill the roles of information strategists, data analysts, and educators, demonstrating proficiency in navigating intricate digital environments. Notwithstanding these advancements, public perception frequently remains outdated, perceiving librarians primarily as engaged in rudimentary administrative activities. This stereotype inhibits the recognition of their extensive contributions to society. Re-branding initiatives center on emphasizing the evolving roles of librarians, which encompass the management of comprehensive digital resources and the promotion of critical information literacy within the context of the artificial intelligence era. The Faculty of Social and Political Sciences (FISIP) at the University of Lampung (Unila), in conjunction with the Association of Indonesian Political Science Students (ATPUSI), has commenced the implementation of training programs aimed at facilitating the re-branding efforts of the institution. These initiatives aim to enhance the digital competencies of librarians and transform public perceptions by positioning them as crucial facilitators in the process of knowledge dissemination. The results of the training indicate a significant enhancement in participants' comprehension of personal re-branding, thereby suggesting the efficacy of these initiatives in preparing librarians with the requisite skills for a future increasingly influenced by artificial intelligence. Keywords: librarian re-branding, artificial intelligence (AI) era, librarian skill improvement.